STANDARISASI DOKUMEN KELENGKAPAN ITSM UNTUK AREA TECHNICAL SUPPORT MENGGUNAKAN ISO 20000 PADA DIVISI IT PT RALALI - Nurfitria Khoirunnisa; Nunu Nugraha Purnawan; Mona Parlinggoman Siregar (Pusat Riset dan Inovasi Nasional, 2022)
Organizations is one of the parts that use information technology, both business/profit-oriented organizations known as companies and non-profit organizations. Implementation of ITSM in an organization or IT division will be very helpful to increase the role of IT actively to help develop or support the company's business. In this process, IT in an organization will also be easier to develop and improve in terms of service quality, if the organization has implemented standardized service management (ITSM). This study aims to analyze and discuss about IT Service Management. PT Ralali is an IT company that focuses on providing a shopping platform for the first business needs in Indonesia. PT Ralali connects millions of vendors and MSMEs so they can start and grow their business. The current condition based on the results of the study illustrates that PT Ralali has not implemented ITSM, this is the findings of the checklist carried out on the ISO standard service delivery process. Through this research, it is known that there is a significant gap from what PT Ralali has done today compared to the standards held by ISO 20000, so that based on this gap, ITSM implementation can be proposed in the technical support area according to the company's needs and adapted to the scope Research area.